English Learning Approach in Improving Speaking and Listening Skills at Senior Senior High School in Indonesia - Sholeh, Muh Ibnu; Singh, W. C.; Sahri,; Sokip, (BRU ELT JOURNAL, 2023)
This research aims to analyze how the English language learning approach can improve speaking and listening skills at Gunungjati Senior Senior High Schooland Sunan Kalijaga Senior Senior High School. This research method uses qualitative research. The research location was at two schools, namely Senior High School Gunungjati and Senior High School Sunan Kalijaga Tulungagung Indonesia. Data was collected through classroom observations, interviews with teachers, and evaluation of teaching materials. In addition, surveys and exams are conducted to measure students' progress in speaking and listening. The data collected was analyzed using qualitative analysis methods consisting of the process of transcription, coding, grouping the essence of research results that have the same meaning, and presenting the data. The research results show that Senior High School Gunung Jati has succeeded in carefully implementing a project-based approach, creating a learning context that reflects real-world situations. These projects motivate students to speak English and collaborate actively. Sunan Kalijaga Senior High School has successfully used a technology-based approach in learning English. The use of podcasts, mobile applications, and other audio materials has helped students improve their listening skills. The success of both approaches depends on teacher preparation, adaptation of learning content, and selection of relevant technology.